Burnout Syndrome During the Covid-19 Pandemic among Visual Art Teachers in Ghana - Mavis Osei; Dickson Adom; Ampofo Kwene; Nicholas Tetteh (Indonesia Approach Education, 2021)
This study sought to address burnout syndrome during the COVID-19 global pandemic among visual art teachers in Ghana. The startling intricacies of COVID-19 burnout among Visual Art Teachers (VAT) in Ghana were discovered using an exploratory research approach. 112 participants were surveyed across Senior High Schools Visual Art Teachers in Ghana. Data were analyzed using t-test, regression, and analysis of variance test (F test) to determine whether there were significant differences between the burnout levels and demographic factors. The findings revealed that, the only effects of the burnout that are statistically significant on gender are reduction in productivity or efficacy in teaching difference (t=-4.41, p=0.00(p<0.05)), Sleep disorders (t= -3.22, p=0.02(p<0.05)), short temper (t=-2.84, p=0.006(p<0.05)) and health consequences (t=3.36, p=0.001(p<0.05)). The ANOVA was significant between burnout negative effect among education level F (3, 108) =2.983, p= .035. However, the ANOVA was insignificant between burnout causes, effects, and preventive strategies scores and the ages of the teachers. The findings revealed that the majority of suggestions for burnout prevention fall under the category of personal changes. The study contends that though job responsibilities are high, the primary idea is that individuals have a larger role to play in preventing burnout.